Inoculation with indigenous nitrogen-fixers enhances seedling growth and nutrient uptake in a greenhouse bioassay - Majda K. Suleiman; Ali M. Quoreshi; Anitha J. Manuvel; Mini T. Sivadasan; Sheena Jacob (PLoS ONE, 2026)
Desert ecosystems in Kuwait are increasingly affected by land degradation, resulting in nutrient-limited soils that constrain native plant establishment. Harnessing indigenous diazotrophic bacteria adapted to arid environments may provide a sustainable strategy to improve plant growth and nutrient acquisition. Free-living and root-associated nitrogen-fixing bacteria contribute substantially to nitrogen inputs in arid ecosystems and may enhance plant growth, performance and nutrient acquisition under nutrient-poor conditions. This study evaluated the growth performance and nutrient uptake ability of four native plant species of Kuwait following inoculation with a consortium of selected indigenous putative diazotrophs isolated from the Kuwait desert soils. The seedlings of Vachellia pachyceras were inoculated with both indigenous root-nodule bacteria isolated from Kuwait desert and a commercial inoculum to evaluate their symbiotic efficiency. The seedlings were cultivated under greenhouse conditions using either native desert soils or a potting mix substrate to assess the influence of growth medium or inoculation response. Across species, inoculation significantly enhanced plant dry mass and nutrient uptake compared to the non-inoculated controls. The magnitude of improvement varied among bacterial density, host plants, and growth substrate. These findings support the potential use of indigenous diazotrophs as biofertilizers to enhance plant growth and nutrient uptake of native plant species, and for restoration and revegetation efforts in arid environments. However, direct measurements of nitrogen fixation were not conducted and should be addressed in future field-based studies. This study represents the first evaluation of Kuwait’s native seedlings inoculated with indigenous diazotrophs, highlighting their potential for sustainable ecosystem restoration.